1979
DOI: 10.1139/f79-204
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride in Antarctic Krill (Euphausia superba) and Atlantic Krill (Meganyctiphanes norvegica)

Abstract: Samples of Antarctic krill (Euphausia superba) and Atlantic krill (Meganyctiphanes norvegica) were analysed for fluoride using a selective fluoride electrode method. Both species showed very high concentrations, a total of 1330–2400 mg F−/kg on fat free dry weight basis in raw samples whereas deep sea prawns (Pandalus borealis) showed a total of 18–91 and red feed (Calanus finmarchicus) 10–37 mg F−/kg. Sections of Antarctic krill were analyzed, and the highest concentration was found in the carapace, 4260 mg F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 0 publications
3
45
0
Order By: Relevance
“…Fluorides derive principally from the weathering of fluoride minerals and volcanic activity although a small proportion is contributed by the use of aerosols. The fluoride content of Northern krill, in agreement with what is known of other euphausiids, is quite high compared to other oceanic invertebrates with whole body burdens of 2360 mg F À g À 1 dry weight (DW) (Soevik and Braekkan, 1979) and 2153 mg F À g À 1 DW (Adelung et al, 1987). Adelung et al (1987) showed that most of the fluoride was incorporated into the exoskeleton (3343 mg F À g À 1 DW), with relatively small amounts found in the tissues (e.g.…”
Section: Fluoride Accumulation and Regulationsupporting
confidence: 71%
“…Fluorides derive principally from the weathering of fluoride minerals and volcanic activity although a small proportion is contributed by the use of aerosols. The fluoride content of Northern krill, in agreement with what is known of other euphausiids, is quite high compared to other oceanic invertebrates with whole body burdens of 2360 mg F À g À 1 dry weight (DW) (Soevik and Braekkan, 1979) and 2153 mg F À g À 1 DW (Adelung et al, 1987). Adelung et al (1987) showed that most of the fluoride was incorporated into the exoskeleton (3343 mg F À g À 1 DW), with relatively small amounts found in the tissues (e.g.…”
Section: Fluoride Accumulation and Regulationsupporting
confidence: 71%
“…*Not detectable (ND). Krill contains a high amount of fluoride mainly derived from the exoskeleton (Soevik and Braekkan, 1979;Schneppenheim, 1980;Adelung et al, 1987;Sands et al, 1998). Grave (1981) investigated the uptake of fluoride from Antarctic krill by salmonids in brackish water for up to 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…In our study the krill collected from the stomach of the whales was partially digested, so neither the molting state nor the species composition could be established. However, previous studies have shown that the diet of North Atlantic fin whales is mainly composed of M. norvegica in both areas (Soevik and Braekkan, 1979;Aguilar 1985;Sigurjónsson and Víkingsson, 1997), and the difference between areas was found to be so large that within-areas variation was considered not able to obscure it. Thus, concentrations of fluoride were significantly higher in the krill from W Iceland than in that from NW Spain.…”
Section: Tablementioning
confidence: 82%
“…Soevik and Braekkan (1979) found levels of fluoride in the range 1330-2400 mg kg À1 fat free dry weight in whole body of North Atlantic Meganyctiphanes norvegica and Antarctic Euphausia superba, and Sands et al (1998) reported levels of up to 5977 mg kg À1 dry weight in the exoskeleton of Antarctic Euphausia crystallorophias and of 12800 mg kg À1 dry weight in the mouth parts of Antarctic E. superba. Consistently with these high levels in krill, most vertebrates feeding on these krill, such as Adélie penguins (Pygoscelis adeliae), crabeater seals (Lobodon carcinophagus), minke whales (Balaenoptera acutorostrata) and fin whales (Balaenoptera physalus), also show high fluoride content in their bones and other skeletal structures (Schneppenheim, 1980;Adelung et al, 1985;Walton, 1988;Landy et al, 1991;Alne, 1995).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation